DNA methylation and mRNA expression of glutathione S-transferase alpha 4 are associated with intracranial aneurysms in a gender-dependent manner - Xu, Tianqi; Yu, Xi; Zhou, Shenjun; Wu, Yiwen; Deng, Xinpeng; Wu, Yuefei; Wang, Shiyi; Gao, Xiang; Nie, Sheng; Zhou, Chenhui; Sun, Jie; Huang, Yi (Frontiers in Genetics, 2023)
Objective: We performed a case-control study to investigate the correlation between DNA methylation and mRNA expression of the glutathione S-transferase alpha 4 (GSTA4) gene and the risk of intracranial aneurysm (IA) in the Chinese Han population. Methods: After propensity score matching, 44 pairs of cases and controls were collected in this study. Fasting blood samples were collected for DNA and RNA extraction within 24 hours of admission. Nine CpG dinucleotides were selected from the GSTA4 promoter region for DNA methylation pyrosequencing. mRNA expression of GSTA4 was measured by quantitative real-time polymerase chain reaction (RT-qPCR). In vitro cell experiments were conducted to verify the association between 5-aza-2′-deoxycytidine induced DNA hypomethylation and GSTA4 mRNA expression. Results: The mean methylation level of GSTA4 was much lower in IA patients, especially in UIA, than that in controls (IA vs. Control, p < 0.001; RIA vs. Control, p = 0.005; UIA vs. Control, p < 0.001). With sex stratification, we further found that the association between GSTA4 methylation and IA risk presented only in women (mean methylation level: IA vs. Control, p < 0.001; RIA vs. Control, p = 0.009; UIA vs. Control, p < 0.001). GSTA4 mRNA expression was significantly higher in the IA group than in the control group (p < 0.01) and negatively correlated with DNA methylation in all individuals (r = −0.746, p < 0.001). DNA hypomethylation can increase GSTA4 mRNA expression in human primary artery smooth muscle cells. The receiver operating characteristic (ROC) curve showed that GSTA4 mean methylation (AUC = 0.80, p < 0.001) was a reliable predictor of women IA, among which CpG 1 exhibited the best predictive value (AUC = 0.89, p < 0.001). In addition, GSTA4 expression levels could also predict the risk of IA in women (AUC = 0.87, p = 0.005). Conclusions: Decreased DNA methylation and increased mRNA expression of the GSTA4 gene are associated with the risk of IA in women.